Pengembangan E-Module Pembelajaran Berbasis Android untuk Meningkatkan Pemahaman Siswa pada Materi Sistem Rem Antilock Breaking System di SMK Teuku Umar Semarang - Yuliyanto, Diky; Abdurrahman, Abdurrahman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This research aims to develop an Android-based learning e-module to increase students' understanding of the Antilock Braking System (ABS) brake system material at SMK Teuku Umar Semarang. The research method uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research subjects involved 30 students and 2 subject matter experts. The pre-test results showed an average score of 70.4 which increased to 80.8 in the post-test, with an n-gain value of 0.3513 (medium category). The e-module feasibility assessment by subject matter experts and students obtained an average score of 94.375% (very feasible category). The results of the study show that Android-based e-modules are effective in improving students' understanding of ABS brake system materials and are suitable for use as a learning medium in vocational schools. Based on these results, it shows that the use of Android-based e-modules is effective in increasing students' understanding of ABS brake system materials, and is suitable for use as a learning medium in vocational schools.